STATE POLICY IN ENGINEERING EDUCATION: THE REGIONAL VIEW - Vasily G. Ivanov; Leysan R. Abzalilova (Высшее образование в России)
The article deals with topical issues of modern engineering education development which require, due to the Russian specific character, the state participation and employer’s attention. During the last years, state support of higher technical education has been reshaping. The accent has been done on a public–private partnership. KNRTU has created its own innovation model of this type of partnership.